HUMAN RIGHTS AWARENESS AMONG POST GRADUATE STUDENTS WITH SPECIAL REFERENCE TO PITHORAGARH DISTRICT - Kandpal, Rakshita; Joshi, Anita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Human rights refer to the fundamental freedoms, without which men, women and children cannot live with respect and dignity. Basics to human rights are the values of non-discrimination and equality, which contribute to building a culture of peace in society. In this study an attempt has been made to investigate the awareness of human rights among post-graduate students studying in the L.S.M. Campus, Pithoragarh and Government postgraduate college, Berinag. In the present study descriptive survey method was adopted. Simple random sampling technique was used to select samples of 100 post graduate students with the objective to study level of human rights awareness and to compare human rights awareness with respect to gender, academic stream and nature of residence among post-graduate students. A standardised Human Rights Awareness Test by Vishal Sood & Arti Anand,(2012) was used to collect the data. To analyse the data mean, standard deviation and t-test was used. The findings of the study reveals that majority of the students (42 percent) showed averege level of awareness.On the other hand female post gradaute students, urban residing and having Science stream students have shown more awareness. So, there is a need to provide human rights education in schools and colleges. Human Rights Education mission is to encourage personal growth and acceptance of others to foster cooperation and peace among individuals and countries. Students’ awareness of human rights helps in transferring the same to future citizens. Hence adequate awareness in them can help to create a sensitive, informed, and enlightened society.